"Deutschland kann nur durch Deutschland gerettet werden": der Kampf um das nationale Erbe der Befreiungskriege am Berliner Dönhoffplatz im 19. und 20. Jahrhundert - Haase, Christian; Kreuzer, Jörn (University of Nottingham, 2011)
The former Dönhoffplatz has been renamed the Marion-Gräfin-Dönhoff-Platz in 2010. The University of Nottingham provided the historical background research on the history of the Platz which dates back to the 1740s. The findings are presented in this Preprint version and add to the information on the memorial plate on the Platz.